Analysis of Investment Decisions, Funding Decisions and Psak Compliance with Corporate Social Responsibility Disclosure (Csrd), Financial Performance, and Audit Opinions with Good Corporate Governance as Moderation in Indonesia State Enterprises - Hendy Widiastoeti; Tri Ratnawati; Mulyanto Nugroho (LPPM of NAROTAMA UNIVERSITY, 2021)
The research gap in this study with previous research is in the first study of Ahmed A. Diab, Samir I. Abdelazim, Aref M. Eissa, Eid Mahmoud Abozaid, Mona Mohamed Elshaabany, where previous research only examined company size and financial performance on audit opinion in 2012-2016, while this research is on State-Owned Enterprises (BUMN) listed on the Indonesian Stock Exchange. In addition, there have not been many previous studies similar to this research, but the research has a novelty in the form of the absence of a comprehensive study that examines the variables of Investment Decisions, Funding Decisions, PSAK Compliance, on Audit Opinion with CSRD and Financial Performance as Intervening variables. and GCG as Moderating Variable. The purpose of this study is to analyze the effect of investment decisions, funding decisions, PSAK compliance, on audit opinions. CSRD and Financial Performance variables as Intervening variables on CSRD, Financial Performance and Audit Opinion with GCG as moderating in BUMN companies on the Indonesia Stock Exchange. The quantitative research method is Causal Explanatory with the unit of analysis as many as 23 Non-Bank BUMN companies during the 2017 to 2019 research period so that a total of 69 samples were processed using SmartPLS 3.0. The results showed that 14 hypotheses were accepted, meaning that there was a significant effect on Investment Decisions, Funding Decisions and PSAK Compliance on CSRD, Financial Performance and Audit Opinions. Meanwhile, GCG is proven to moderate the influence of Financial Performance on Audit Opinion (H13), while one hypothesis, namely H12, is rejected. This means that GCG does not moderate the influence of CSRD on Audit Opinion